Thank you for the opportunity to help you with your question!

Hey I will provide the best answers for you , But there are so many questions and $1 is not worth doing this much

so I will explain 1st question

if x> 2 then x^2 - x -6 / x^2 -4

first x^2 -4 = (x+2) (x-2) [ based on formula (a+b) (a-b) = a^2 - b^2 ]

and x^2 - x -6 = x^2 -3x +2x +6

= x(x-3) +2 (x+3)

= (x+2) (x -3)

so if x> 2 then x^2 - x -6 / x^2 -4 = [ (x+2) (x-3) ] / [ (x+2) (x-2) ]

= x - 3 / x -2 ------->B

2). 4 - (-6) / -5 = 4 + 6 / -5 = 10 / -5 = -2 --->D

post other question separatly

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up